Examination of the Amount of Atmospheric Precipitation: Case Study – Middle Zarafshan River Basin - Juraev Zuhriddin; Ziyaev Rahmat; Khikmatov Fazliddin (Mediterranean Journal of Social Sciences, 2023)
In this study, the fluctuating precipitation in Central Asia’s Middle Zarafshan basin was examined. Investigating the seasonal variation and distribution of atmospheric precipitation in this area was the goal of this study. Changes in the amount of atmospheric precipitation seen over the primary and current climate periods were taken into consideration using data from 13 meteorological stations located in the basin's plains and mountainous regions. Calculations were made on changes in atmospheric precipitation by altitude zones throughout various climatic eras, and differences in annual fluctuations and distribution changes over time were displayed. Received: 26 March 2023 / Accepted: 28 June 2023 / Published: 5 July 2023